Novel Hybrid Conductor of Irregularly Patterned Graphene Mesh and Silver Nanowire Networks - Hiesang Sohn; Weon Ho Shin; Dohyeong Seok; Taek Lee; Chulhwan Park; Jong-Min Oh; Se Yun Kim; Anusorn Seubsai (Micromachines, 2020)
We prepared the hybrid conductor of the Ag nanowire (NW) network and irregularly patterned graphene (GP) mesh with enhanced optical transmittance (~98.5%) and mechano-electric stability (ΔR/Ro: ~42.4% at 200,000 (200k) cycles) under 6.7% strain. Irregularly patterned GP meshes were prepared with a bottom-side etching method using chemical etchant (HNO3). The GP mesh pattern was judiciously and easily tuned by the regulation of treatment time (0–180 min) and concentration (0–20 M) of chemical etchants. As-formed hybrid conductor of Ag NW and GP mesh exhibit enhanced/controllable electrical-optical properties and mechano-electric stabilities; hybrid conductor exhibits enhanced optical transmittance (TT = 98.5%) and improved conductivity (ΔRs: 22%) compared with that of a conventional hybrid conductor at similar TT. It is also noteworthy that our hybrid conductor shows far superior mechano-electric stability (ΔR/Ro: ~42.4% at 200k cycles; TT: ~98.5%) to that of controls (Ag NW (ΔR/Ro: ~293% at 200k cycles), Ag NW-pristine GP hybrid (ΔR/Ro: ~121% at 200k cycles)) ascribed to our unique hybrid structure.